2016
DOI: 10.4172/2155-952x.1000241
|View full text |Cite
|
Sign up to set email alerts
|

SSR Marker-based Genetic Diversity Analysis of Tidal and Flood Prone Areas in Rice (Oryza sativa L.)

Abstract: One hundred and sixty rice varieties from the tidal and flood prone areas of south and south East Asian countries were analyzed. Samples sizes were: 50 varieties from Bangladesh (deepwater, tidal and flood prone rice and modern varieties), 14 varieties from India (flood prone rice), 16 varieties from Sri Lanka (flood prone rice), 7 varieties from Vietnam (tidal varieties), 69 varieties from Indonesia (tidal varieties) and 4 check varieties from IRRI. All 30 primer pairs created polymorphic bands among the 160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
2
2
0
1
Order By: Relevance
“…This observation corresponds to the previous observations of other rice germplasm studies [42, 43]. In another rice diversity study, 42 colored rice varieties were reported to have clustered according to their country and region of origin [25].…”
Section: Resultssupporting
confidence: 90%
“…This observation corresponds to the previous observations of other rice germplasm studies [42, 43]. In another rice diversity study, 42 colored rice varieties were reported to have clustered according to their country and region of origin [25].…”
Section: Resultssupporting
confidence: 90%
“…All these points to the accuracy and usefulness of the SSR markers in tracing the phylogency or pedigree of a germplasm or breeding materials. These observations, corresponds to the previous observations of other rice germplasm studies (Bonny et al, 2015 andMasuduzzaman et al, 2016). Similarly, a clustering pattern has also been reported by Pachauri et al (2013) based on allelic and morphological data along with the location in rice varieties using SSR markers.…”
Section: Fig 2 Dendrogram Showing the Genetic Dissimilarity Among The Rice Genotypessupporting
confidence: 91%
“…Eleven varieties from different haplotypes (Masuduzzaman et al, 2016), differing in tolerance (Table 4) were examined. For assaying Sub1A and Sub1C expression, 4 sets of seedlings of 11 varieties were raised in separate plastic trays, containing grinded soils.…”
Section: Plant Materials and Submergence Treatmentmentioning
confidence: 99%
“…Recent study of Masuduzzaman et al (2016) identified few more tolerant genotypes, those are distinct from 'FR13A' (non-Sub1 type of tolerant, Madabaru, Kottamali). Efforts are needed to investigate strengths of transcriptional interactions of alleles related to tolerance.…”
Section: Introductionmentioning
confidence: 99%